Evaluating Shared Decision Making in Trial of Labor After Cesarean Counseling Using Objective Structured Clinical Examinations - Brownsyne Tucker Edmonds; Shelley M. Hoffman; Tatiana Laitano; Fatima McKenzie; Janet Panoch; Abigail Litwiller; Mark J. Di Corcia (Association of American Medical Colleges, 2020)
Introduction Although shared decision making (SDM) is optimal for trial of labor after cesarean (TOLAC) counseling, resources to assess residents' clinical competency and communication skills are lacking. We addressed this gap by developing and testing an objective structured clinical examination (OSCE) to evaluate whether learners were able to use SDM in TOLAC counseling. Methods We created three simulation scenarios with increasing complexity to assess the skills of residents in their first, second, or third postgraduate year in using SDM in TOLAC counseling. All cases involved a standardized patient requesting a TOLAC consultation. Residents were provided with a medical history and instructed to counsel and develop a care plan. A 10-item scoring rubric was used, and each item was rated 0 (absent), 1 (partial), or 2 (complete). Three coders independently rated the encounters; discrepancies were resolved by consensus. Results Over 3 years, 39 residents participated in 60 OSCE encounters. The majority provided complete discussions of the clinical issue (93%), chances of success (72%), and maternal and fetal risks (100% and 85%, respectively) but obtained partial assessments of understanding (78%). Discussions of benefits were typically absent, with the exception of the maternal benefits (47%). More than 40% of residents did not discuss the patient's goals, 53% lacked discussion of uncertainties related to TOLAC, and half failed to explore the patient's preference, with most deferring a decision to a future encounter. Discussion Residents consistently discussed diagnosis, prognosis, and maternal risks yet infrequently addressed goals and preferences-two critical elements of SDM.